A stable metallic 3D porous BPC2 as a universal anode material for Li, Na, and K ion batteries with high performance. Issue 48 (11th December 2020) - Younis, Umer; Muhammad, Imran; Qayyum, Fizzah; Kawazoe, Yoshiyuki; Sun, Qiang
Abstract : Materials composed of B, C, and P have been hotly pursued for batteries due to their low mass and high abundance. Abstract : Materials composed of B, C, and P have been hotly pursued for batteries due to their low mass and high abundance. However, all the reported 3D B–C–P compounds at present are semiconductors with low electrical conductivity. Motivated by the semi-metallic character of a stable 2D-BPC2 sheet, we propose the first metallic porous 3D structure by using BPC2 nanoribbons as the basic building blocks. Based on ab initio calculations, we find that the 3D porous BPC2 is highly stable dynamically and thermally. The exhibited intrinsic metallicity together with the unique morphology makes this porous structure a universal anode material for Li, Na, and K-ion batteries with high theoretical capacities of 407.29, 407.29, and 305.48 mA h g −1, low diffusion barriers of 0.29, 0.05, and 0.03 eV, and small volume expansions of 0.25, 1.15, and 1.55%, respectively. These intriguing findings should stimulate experimental effort on synthesizing a metallic 3D porous universal anode for multi-ion batteries.